mPW1PW91 Calculated Structures and IR Spectra of Thiacalix[4]biscrown-5 Complexed with Alkali Metal Ions - Choe, Jong-In (Bulletin of the Korean Chemical Society, 2011)
The molecular structures of thiacalix[4]biscrown-5 (1) and p-tert-butylthiacalix[4]biscrown-5 (2) and their alkali-metal-ion complexes were optimized using the DFT BLYP/6-31G(d) and mPW1PW91/6-31G(d,p)(hybrid HF-DF) calculations. The total electronic energies, the normal vibrational modes, and the Gibbs free energies of the mono- and di-topic complexes of each host with the sodium and potassium ions were analyzed. The K^+-complexes exhibited relatively stronger binding efficiencies than Na^+-complexes for both the monoand di-topic complexes of 1 and 2 comparing the efficiencies of the sodium and potassium complexes with an anisole and phenol. The mPW1PW91/6-31G(d,p) calculated distances between the oxygen atoms and the alkali metal ions were reported in the alkali-metal-ion complexes (1•Na^+, 1•2Na^+, 1•K^+, 1•2K^+, 2•Na^+, 2•2Na^+, 2•K^+,2•2K^+). The BLYP/6-31G(d) calculated IR spectra of the host 1 and its mono-topic alkali-metal-ion complexes are compared. KCI Citation Count: 13